What are the determinants of health care expenditure? Empirical results from Asian countries - Furuoka, Fumitaka *; Lim, Beatrice Fui Yee; Kok, Emily; Mohammad Zahirul Hoque,; Munir, Qaiser (Sunway University, 2011)
This paper uses panel data to identify the determinants of health care expenditure in twelve Asian countries (i.e. Cambodia, China, Indonesia, Japan, Laos, Malaysia, Mongolia, the Philippines, South Korea, Singapore, Thailand and Vietnam) for the period of 1995-2008. The empirical results indicated that only two independent variables (GDPit and POP65it) have significant relationship with health care expenditure in these countries. These two variables are positively correlated with the amount of health care expenditure. In other words, when the countries’ income is larger, the amount of health care expenditure is larger. When the share of ageing population in the total population is higher, again the amount of health care expenditure is larger.